2005
DOI: 10.1007/s00204-005-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Subacute oral toxicity study of diethylphthalate based on the draft protocol for “Enhanced OECD Test Guideline no. 407”

Abstract: We performed a 28-day repeated-dose toxicity study of diethylphthalate based on the draft protocol of the "Enhanced OECD Test Guideline 407" to investigate whether it has endocrine-mediated properties according to this assay. Diethylphthalate was orally administered to SD rats at doses of 0, 40, 200, and 1,000 mg/kg/day for at least 28 days, but no endocrine-mediated effects were detected based on any of the parameters examined, suggesting that diethylphthalate does not possess endocrine properties according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
16
1
Order By: Relevance
“…In addition, serum and testicular testosterone levels were statistically significantly decreased in young rats exposed to DEP for 7 days ( Oishi and Hiraga 1980 ), although this data was presented as a percentage of control without a measure of variance and is considered low confidence . In contrast to other findings, no effect on serum testosterone or gonadotropin levels was observed in a high confidence study in Wistar rats following exposures up to 1000 mg/kg-day DEP for 28 days ( Shiraishi et al 2006 ), although those authors did observe a statistically significant decrease in serum estradiol for males in the 1000 mg/kg-day dose group. No effects on serum testosterone were observed in a medium confidence study in Swiss albino mice following exposures up to 10 mg/kg-day in diet for 3 months ( Mondal et al 2019 ).…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…In addition, serum and testicular testosterone levels were statistically significantly decreased in young rats exposed to DEP for 7 days ( Oishi and Hiraga 1980 ), although this data was presented as a percentage of control without a measure of variance and is considered low confidence . In contrast to other findings, no effect on serum testosterone or gonadotropin levels was observed in a high confidence study in Wistar rats following exposures up to 1000 mg/kg-day DEP for 28 days ( Shiraishi et al 2006 ), although those authors did observe a statistically significant decrease in serum estradiol for males in the 1000 mg/kg-day dose group. No effects on serum testosterone were observed in a medium confidence study in Swiss albino mice following exposures up to 10 mg/kg-day in diet for 3 months ( Mondal et al 2019 ).…”
Section: Resultscontrasting
confidence: 70%
“…The medium confidence study by Mondal et al (2019) reported a statistically significant decrease in epididymal sperm count, motility, and viability and increased sperm morphological abnormalities in adult mice dosed with 1 or 10 mg/kg-day for three months, and provided supporting mechanistic evidence demonstrating oxidative stress in germ cells and apoptosis in testicular sections. Conversely, the medium confidence study by Shiraishi et al (2006) reported no effects on epididymal sperm counts or morphology in adult rats following 28-day DEP exposure at doses up to 1000 mg/kg-day, although the authors provided no quantitative data. Although effects varied across studies, alterations in sperm quality were observed across most studies including three considered high confidence , and therefore the evidence for effects on sperm parameters is considered moderate.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study investigating MPB exposure and estrogenic effects, MPB was administered by oral gavage from PND 21 to 40 in oral doses ranging from 62.5 to 1,000 mg/kg/day ( Vo et al 2010 ). In another investigation of DEP exposure and endocrine-mediated properties, the chemical was administered by oral gavage for 28 days in doses ranging from 40 to 1,000 mg/kg/day ( Shiraishi et al 2006 ). In most cases, the lowest doses far exceeded the highest doses (0.25 mg/kg/day for triclosan, 5.25 mg/kg/day for MPB, 8.675 mg/kg/day for DEP) used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to evaluate risks or investigate the biological effects of environmental chemicals, it is critical to employ doses in animal experiments that are comparable to the human experience. However, the dose ranges used for DEP, MPB, and triclosan in animal studies have been wide and often orders of magnitude higher than humans are likely to encounter ( Shiraishi et al 2006 ; Stoker et al 2010 ; Vo et al 2010 ). On the basis of increasing evidence suggesting low-dose health effects of these chemicals, there is an urgent need for studies that utilize doses in the range of typical human exposure ( Birnbaum 2012 ; Casals-Casas and Desvergne 2011 ).…”
Section: Introductionmentioning
confidence: 99%